2022
DOI: 10.1021/acsomega.2c06150
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Fungal Activity of Moutan cortex Extracts against Rice Sheath Blight (Rhizoctonia solani) and Its Action on the Pathogen’s Cell Membrane

Abstract: Rice sheath blight (RSB) caused by Rhizoctonia solani is one of the most destructive diseases of rice (Oryza sativa). Although chemical fungicides are the most important control methods, their long-term unreasonable application has brought about problems such as environmental pollution, food risks, and non-target poisoning. Therefore, considering the extraction of fungistatic substances from plants may be an alternative in the future. In this study, we found that the Moutan cortex ethanol extract has excellent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…The fungal cell wall is a dynamic skeleton with high plasticity that protects the cell from different stresses . It has been reported that some natural antifungal compounds that damage the cell membrane could target the cell wall at the same time . To explore the effects of 2,4-DTBP on the cell wall integrity of U.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fungal cell wall is a dynamic skeleton with high plasticity that protects the cell from different stresses . It has been reported that some natural antifungal compounds that damage the cell membrane could target the cell wall at the same time . To explore the effects of 2,4-DTBP on the cell wall integrity of U.…”
Section: Resultsmentioning
confidence: 99%
“…22 It has been reported that some natural antifungal compounds that damage the cell membrane could target the cell wall at the same time. 23 To explore the effects of 2,4-DTBP on the cell wall integrity of U. virens, mycelia were stained with CFW, which is a specific fluorescent dye that could bind to chitin at the fungal cell wall and emit blue fluorescence. 24 As shown in Figure 6, all of the mycelia exhibited blue fluorescence.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The method of petroleum ether extract preparation of MC was by the cold-soaking method. [21] MC was crushed and sieved using a 60 mesh sieve. Next, it was weighed to 30 g and dissolved in 300 mL of petroleum ether at room temperature.…”
Section: Preparation Of Petroleum Ether Extract Of MCmentioning
confidence: 99%
“…Additional extraction work demonstrated that the active component was primarily present in the petroleum ether extract. [21] However, the chemical components of MC petroleum ether extract that exert the main antifungal activity are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the expanding population and growing food demands, rice ( Oryza sativa L.), one of the most widely consumed cereal crops in the world, is of great importance to feed the increasing population. , Rhizoctonia solani is a highly detrimental fungus to rice crops, with the potential to cause rice sheath blight (ShB) and result in significant reductions in both the yield and quality of rice. For instance, this fungi results in significant yield losses of rice up to 50% in some South Asian countries such as China and India. , Up to date, chemical fungicides remain the most efficient and dependable means for controlling R. solani.…”
Section: Introductionmentioning
confidence: 99%